How breastfeeding and nutrition can impact the intestinal microbiota in the child's development (Research, Society and Development, 2023)
The infant gut microbiota undergoes a number of considerable developments in the first few years of life, and some of the factors that are connected to this are breastfeeding and early complementary feeding. The study aims to show how breastfeeding and food are extremely important to develop the child's microbiota and point out possible harm if not followed correctly. The methodology used was a narrative literary review, the articles were analyzed in the following languages: Portuguese, English and Spanish and the period of inclusion for analysis of the articles was from 2017 to 2023. The intestinal microbiota formed at birth is influenced by breastfeeding, time of breastfeeding and feeding. And breast milk contributes to building the immune system that attributes lifelong protection of the individual against numerous diseases. The Nutritionist has full capacity and duty to guide mothers on the importance of breastfeeding and complementary feeding, showing how breastfeeding helps the health of the newborn and help with possible problems at the time of breastfeeding and monitoring the introduction of complementary feeding. so that the child can have a healthy intestinal microbiota, and thus a better quality of life.